Hubungan Indeks Massa Tubuh (IMT) dengan Ankle Brachial Index (ABI) pada Pasien Diabetes Mellitus Tipe 2 Etnis Jawa - Yanuarita Tursinawati; Arum Kartikadewi; Kamala Nuriyah; Setyoko Setyoko; Ari Yuniastuti (Politeknik Kesehatan Tanjung Karang, 2020)
Diabetes mellitus (DM) often give a macrovascular complication such as Peripheral arterial disease (PAD). Ankle-brachial index (ABI) is a sensitive and specific examination for PAD. Obesity can be a risk factor of PAD. Obesity can be classified by the BMI (Body Mass Index) classification. The purpose of this research is to analyze the relationship of BMI with ABI in Type 2 DM (T2DM) patients of Javanese ethnicity. This study was an observational analytic research with case-control design and used a purposive sampling technique. There were 40 case samples and 40 control samples. Data analysis used the Independent T-test and Chi-square test. There was a significant differences on age (p=0,000), METs (p-value=0,003), and ABI (p-value=0,002) between the two groups. In the DM group was found that most abnormal ABIs were found in the higher BMI, even though there was no significant correlation by the statistic (p-value=0,255). BMI contributed less to the ABI value of Javanese ethnic T2DM patients.